Simulation of light propagation in citrus fruit using monte carlo multi-layered (MCML) method. (February 2021) - Sun, Chanjun; Aernouts, Ben; Van Beers, Robbe; Saeys, Wouter
Abstract: The interaction of visible and near-infrared light with citrus tissues is of great importance for the design of new optical sensors for fruit quality inspection. In this study, the light propagation through citrus fruit was simulated using the Monte Carlo multi-layered (MCML) technique based on the bulk optical properties (BOP) of citrus tissues. Comparison of the diffuse reflectance profiles from MCML and from the laser scatter images confirmed the accuracy of the simulations. Simulation results indicated that most of the light was diffusely reflected or absorbed in the flavedo. Only a small fraction around 800 nm was transmitted through the three layers. Flavedo and albedo were found to contribute mostly to the diffuse reflectance spectra at 800 nm and their contributions respectively decreased and increased with source-detector distance. Although the contribution of juice vesicles increased with distance, the maximal diffuse reflectance intensity contributed by juice vesicles was located within 0.56 cm. Based on these results, the combination of the power intensity and the source-detector distance can be optimized to obtain more information about the layer of interest, which lays the foundations for designing new quality detection sensors for citrus fruit. Highlights: Light propagation in citrus fruit was simulated by Monte Carlo multi-layered model. Good agreement of simulated and measured diffuse reflectance profiles. Light was mainly absorbed by flavedo and diffusely reflected. Flavedo and albedo contributed mostly to the diffuse reflectance spectra.